The Implementation of Sufism Values: An Effort to Improve Morality in Addressing Contemporary Juvenile Delinquency - Bokhari (Formad English Foundation NTB Jakarta, 2026)
The increasing phenomenon of juvenile delinquency and moral decline among adolescents highlights the urgent need for educational approaches that integrate spiritual and ethical development. This study aimed to examine the implementation of Sufism values in improving adolescent morality and to analyze their contribution to addressing contemporary juvenile delinquency. The research employed a qualitative library research design by analyzing relevant literature from books, scholarly journals, and academic documents related to Sufism, moral education, and youth behavior. Data were collected through systematic literature searches and analyzed using qualitative content analysis and thematic analysis to identify conceptual patterns and relationships among variables. The findings revealed that Sufism values provide a holistic framework for moral development grounded in spiritual purification, ethical awareness, and behavioral transformation. Core values such as sincerity, patience, humility, spiritual consciousness, and compassion were found to strengthen adolescents’ self-control, emotional regulation, and moral responsibility. The implementation of these values occurred through experiential spiritual practices, mentoring, communal religious activities, and role modeling within educational and social environments. Furthermore, Sufism values contributed to preventing juvenile delinquency by fostering moral identity, providing existential meaning and life purpose, and promoting positive peer relationships and social harmony. In conclusion, the integration of Sufism values into educational and community contexts offers a transformative approach to strengthening adolescent morality and addressing behavioral problems. This study contributes to the development of spirituality-based character education by emphasizing internal moral resilience rather than external behavioral control.